Správa daní a poplatků - chybné návaznosti na trestní řízení přetrvávají - Sedláček, Josef (Univerzita Pardubice, 2007)
In the Czech Republic regulates the Tax Act No. 337/1992 Coll. This law makes it easier for criminals its illegal activities. Under that law must not not inform the tax on many offenses, the police, the prosecutor and even the courts. The worst situation was in this area is from the years 1993 to 2004, but even now not all is well.
Keywords: tax administration; economics offences; evade taxes; evade law; criminal procedures; loophole in the law